The IFS Scottish Budget Report: 2025-26 - Stuart Adam; Bee Boileau; Jonathan Cribb; Magdalena Domínguez; Laurence O'Brien; David Phillips; Sam Ray-Chaudhuri; Luke Sibieta; Darcey Snape (Institute for Fiscal Studies (IFS), 2025)
This report analyses the Scottish Government's Budget for 2025-26, with chapters on tax strategy, school spending, public sector pay and more.
Keywords: 330; Education and skills; Employment and income; Government finances and spending; Taxes and benefits; Scotland; Government spending; Tax; Public finance; Property taxes; Devolved government finances; Schools; Pay; Public sector